Analisis Faktor – Faktor Yang Mempengaruhi Impor Beras Di Indonesia - Noerma Yunita Anggraeni; Marseto Marseto; Sishadiyati Sishadiyati (Jurnal Ekonomi, Bisnis dan Manajemen, 2023)
Although Indonesia occupies the third position as a food-producing country in the world, almost every year it faces repeated problems with production, especially rice food production. As a result, Indonesia has to import rice from other food-producing countries. The purpose of this study is to find out what factors affect rice imports in Indonesia. The method used in this study was multiple linear regression analysis. This study concludes that there is simultaneously a significant influence between Rice Production, Rice Price, Population, and Exchange Rate on Rice Imports in Indonesia. Meanwhile, partially Rice Production and Exchange Rate have an insignificant influence, Rice Price and the Population have a significant influence on Rice Imports in Indonesia.